RIDEP 2017
DOI: 10.21865/ridep43_45
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación al Español de la Versión Corta del Inventario de Perfeccionismo Multidimensional en el Deporte en Competición

Abstract: ResumenEl objetivo de este trabajo fue validar la adaptación al español de la versión corta del Inventario de Perfeccionismo Multidimensional en el Deporte (MIPS) en competición, analizando su estructura factorial, invarianza factorial en función del sexo y del tipo de deporte (individual vs. colectivo), y la validez basada en la relación con otras variables. Participaron 295 deportistas de alto rendimiento de ambos sexos quienes respondieron al instrumento. Los resultados confirmaron la estructura bifactorial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 21 publications
(33 reference statements)
1
3
0
1
Order By: Relevance
“…Likewise, Koivula and colleagues’ study [ 36 ] showed that high personal strivings and little concerns over mistakes among Swedish elite athletes (i.e., athletes classified as “positive perfectionists”) predicted relatively high self-confidence and low levels of cognitive and somatic anxiety, as compared to those athletes who exhibited an opposite perfectionism profile (i.e., athletes classified as “negative perfectionists”). This two-fold pattern of relations highlighting the link between strivings for perfection and self-confidence on one side and concerns over “imperfection” and competitive anxiety on the other has been confirmed in other studies conducted with elite athletes [ 31 ], although there are empirical exceptions to this general finding ([ 17 ]; see also the meta-analytical review by [ 12 ]).…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…Likewise, Koivula and colleagues’ study [ 36 ] showed that high personal strivings and little concerns over mistakes among Swedish elite athletes (i.e., athletes classified as “positive perfectionists”) predicted relatively high self-confidence and low levels of cognitive and somatic anxiety, as compared to those athletes who exhibited an opposite perfectionism profile (i.e., athletes classified as “negative perfectionists”). This two-fold pattern of relations highlighting the link between strivings for perfection and self-confidence on one side and concerns over “imperfection” and competitive anxiety on the other has been confirmed in other studies conducted with elite athletes [ 31 ], although there are empirical exceptions to this general finding ([ 17 ]; see also the meta-analytical review by [ 12 ]).…”
Section: Introductionsupporting
confidence: 66%
“…Therefore, any generalization on perfectionism and on its relations with competitive anxiety must be quite cautious. In line with these considerations, recent research [ 28 , 31 ] has stressed the importance of framing future studies of perfectionism within the contexts of specific sports and/or professional agonistic levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puesto que la batería TGMD-2 es un instrumento originalmente creado y validado para la valoración del desarrollo motor, es posible obtener evidencias de validez también a partir de las relaciones de sus factores latentes con otras variables (Pineda-Espejel, Alarcón, López-Walle, & Tomás-Marco, 2017). En relación a la validez concurrente, en el presente estudio se replicó el diseño de Kim et al (2014), por lo que se compararon los valores obtenidos en el conjunto de las habilidades de manejo de objetos, de las de locomoción, así como la puntuación estándar y el cociente de motricidad gruesa obtenidos en la batería TGMD-2 con los resultados de una serie de pruebas de valoración de la condición física.…”
Section: Discussionunclassified
“…To measure perfectionism, we used the short version of the Multidimensional Inventory of Perfectionism in Sport (MIPS) [ 51 ] in its Spanish version adapted by Pineda-Espejel et al [ 52 ]. This instrument comprises ten items that begin with the following phrase, which is adapted to the musical context: “During rehearsal or performance in a show…” Five items assess Factor 1 (F1), “striving for perfection” (e.g., “I have the desire to do everything perfectly”), and the remaining five items assess Factor 2 (F2) “negative reactions to imperfection” (e.g., “I feel completely furious if I make mistakes”).…”
Section: Methodsmentioning
confidence: 99%